PERAN PEREMPUAN SHAHABIYAH DALAM PERIWAYATAN HADITS - Aslamiah, Rabiatul (UIN Antasari Banjarmasin, 2019)
Women in the early days of Islam were given the opportunity as given to mento gain knowledge. To them the Messenger of Allah taught science in the form of his traditions, and they were also permitted to narrate the hadith that they received to others. Women narrated traditions directly from the Prophet, or through friends, both male friends and female friends. The hadiths that they have narrated are many and quite varied, concerning issues of faith and Islam in general, the problem of muamalah, especially matters related to women's issues, family life and household